Periodic solutions for a four-dimensional hyperchaotic system - Yang, J; Wei, Z; Moroz, I (SpringerOpen, 2020)
In this paper, we show a zero-Hopf bifurcation in a four-dimensional smooth quadratic autonomous hyperchaotic system. Using averaging theory, we prove the existence of periodic orbits bifurcating from the zero-Hopf equilibrium located at the origin of the hyperchaotic system, and the stability conditions of periodic solutions are given.